Implementation of Speech Therapy (A, I, U, E, O) in Non-Hemorrhagic Stroke Patients with Verbal Communication Disorder Problems - Karim, Dhimas Ammar Raihan Nur; Hapsari, Agustina Retno; Ngatini, Ngatini (Global Health Science Group, 2024)
Stroke is a condition where blood circulation in the brain occurs due to blockage or bleeding of blood flow to the brain. Non-hemorrhagic stroke patients often experience verbal communication disorders. Treatment of stroke with verbal communication disorders can use pharmacological and non-pharmacological methods such as A, I, U, E, O speech therapy. Determine the level of development of verbal communication in non-hemorrhagic stroke patients. This research uses a descriptive method which aims to describe the patient's condition objectively. The respondent experienced verbal communication disorders so he was given AIUEO speech therapy 2 times a day for 3 days, carried out for 10 minutes with 3 repetitions and there was an increase in the aphasia scale as measured using the DFCS (Derby Functional Communication Scale) scale, the patient's speaking ability increased on the third day. 3 with an aphasia score of 10 or moderate aphasia. A, I, U, E, O speech therapy is able to increase the scale of communication in stroke patients with verbal communication disorders.